DAMPAK BELANJA MODAL TERHADAP NILAI TAMBAH SEKTOR EKONOMI DI PULAU SUMATERA: STUDI EMPIRIS DARI PERSPEKTIF SPASIAL - M. Silahul Mu’min; NAFIS DWI KARTIKO; Muhammad Syariful Anam (Polytechnic of State Finance STAN, 2026)
This study examines how government capital expenditure shapes the value added of three leading sectors in Sumatra: agriculture, mining, and manufacturing. A panel dataset covering all districts and municipalities on the island over the 2010 to 2022 period is analyzed through Geographically Weighted Panel Regression (GWPR) to capture spatial heterogeneity. The estimation reveals that capital expenditure exerts a positive and significant influence on agricultural value added in nearly all localities, whereas its influence on mining and manufacturing differs considerably across space. These findings indicate that well-directed capital budget allocation strengthens sectoral productivity, particularly in agriculture, although its effectiveness is conditioned by local economic characteristics and the quality of budget management in each sector. Local governments are therefore advised to prioritize infrastructure investment that reinforces strategic sectors in order to sustain regional economic growth.